Penerapan Perilaku Hidup Bersih Dan Sehat (PHBS) Di Sekolah Menengah Pertama - Ari Angga Rianto (Jurnal Anestesi, 2023)
PHBS is a form of embodiment of healthy living orientation in individual, family and community culture, which aims to improve, maintain and protect health both physically, mentally, spiritually and socially. The aim of this research is to implement PHBS in schools and encourage every student, teacher and school community to play an active role in creating a healthy school. This research method is comparative analytical with a one group pre-test and post-test design using random sampling, and examination of CO levels. Each participant is given basic education first and then given multiple choice questions consisting of 10 questions. The results of data analysis show that before the counseling was carried out, the majority of respondents had limited knowledge about PHBS in Schools. After attending the counseling there was a significant increase in respondents' knowledge about PHBS in Schools. These results show that counseling is effective in increasing knowledge about PHBS in Schools.